The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1021/ic026115g
|View full text |Cite
|
Sign up to set email alerts
|

The Platinum Catalyst [bpyrPtCl2] in Superacidic Solution

Abstract: The methane oxidation catalyst [bpyrPtCl(2)] (bpyr = bis-pyrimidine) dissolves in superacidic HF/SbF(5) solution under formation of a dinuclear cation [H(2)bpyrPt(mu-Cl)(2)PtbpyrH(2)](6+). Two crystal forms are isolated, [Pt(2)Cl(2)bpyr(2)H(4)](6+)(SbF(6)(-))(4)(Sb(2)F(11)(-))(2).2HF (I) (triclinic, Ponemacr;, a = 814.8(2) pm, b = 1444.8(3) pm, c = 2300.5(5) pm, alpha = 89.627(4) degrees, beta = 84.285(4) degrees, gamma = 84.665(4) degrees, Z = 2) and [Pt(2)Cl(2)bpyrH(4)](6+)(Sb(2)F(11)(-))(6).4HF (II) (tricli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Even Pt metal is dissolved by bpym in hot, 96% H 2 SO 4 to produce homogeneous (bpym)Pt(HSO 4 ) 2 . It has been recently reported that the precatalyst (bpym)PtCl 2 dissolves in superacidic HF/SbF 5 with formation of the dinuclear cation [(H 2 bpym)Pt(μ-Cl)] 2 6+ , which has been crystallographically characterized with SbF 6 - and Sb 2 F 11 2- counterions . It was reported that at temperatures up to about 80 °C this complex shows no reaction with methane (higher temperatures are difficult to handle due to the vapor pressure of HF).…”
Section: “Catalytica” System For Catalytic Methane Functionalizationmentioning
confidence: 99%
“…Even Pt metal is dissolved by bpym in hot, 96% H 2 SO 4 to produce homogeneous (bpym)Pt(HSO 4 ) 2 . It has been recently reported that the precatalyst (bpym)PtCl 2 dissolves in superacidic HF/SbF 5 with formation of the dinuclear cation [(H 2 bpym)Pt(μ-Cl)] 2 6+ , which has been crystallographically characterized with SbF 6 - and Sb 2 F 11 2- counterions . It was reported that at temperatures up to about 80 °C this complex shows no reaction with methane (higher temperatures are difficult to handle due to the vapor pressure of HF).…”
Section: “Catalytica” System For Catalytic Methane Functionalizationmentioning
confidence: 99%
“…Only one comparable structural characterization of both bent and planar isomers has been reported for platinum(II) halo-bridged dimers: it concerns the cationic complex [H 2 bpyrPt( μ -Cl) 2 PtbpyrH 2 ] 6+ (bpyr = bis-pyrimidine) in the salts [Pt 2 Cl 2 bpyr 2 H 4 ] [SbF 6 ] 4 [Sb 2 F 11 ] 2 ·2HF ( θ = 148.4°) and [Pt 2 Cl 2 bpyr 2 H 4 ][Sb 2 F 11 ] 6 ·4HF ( θ = 180°) [ 10 ]. However, unlike the neutral α- and β-trans -Pt 2 ( μ -I) 2 I 2 (CO) 2 species, the difference of the anionic counterpart in these two salts could justify a different stability of two cation forms.…”
Section: Discussionmentioning
confidence: 99%
“…A search on deposited structures in the Cambridge Crystallographic Data Base [ 8 ] with formulae [L 2 Pt( μ -X) 2 PtL 2 ] limited to the halo-bridged items, gave 74 results: 46 chloro-, 20 iodo- and eight bromo-complexes. In 64 of them the coordination squares of the two platinum centres in the molecule are coplanar (or quasi-coplanar), but in eight of them the molecules are bent, showing a θ angle significantly less than 180° [ 3 , 4 , 5 , 9 , 10 , 11 , 12 , 13 , 14 ]. Among the halocarbonyl complexes of platinum(II) [ 15 ] two dinuclear halo-bridged derivatives, namely trans -Pt 2 ( μ -Cl) 2 Cl 2 (CO) 2 [ 16 , 17 ] and trans -Pt 2 ( μ -I) 2 I 2 (CO) 2 [ 18 ], have been structurally characterized and both complexes appear to be essentially planar.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to address these challenges, we aimed to replace bpym with the cationic quaternized nitrogen-containing ligand N -methyl-2,2′-bipyrimidininum ( N -CH 3 -bpym + ). Quaternary nitrogen substituents are highly electron withdrawing; for example, the p K a of N -methylisonicotinic acid (Figure ) is 1.72, which corresponds to a Hammett σ para value of 2.47 for the N -CH 3 group. , We anticipated that the cationic Pt II N -CH 3 -bpym + complex 3 (Figure ) would possess electronic properties similar to those of 2 but would be accessible in the absence of strong acids such as fuming H 2 SO 4 , or HF/SbF 6 . This paper describes studies on the synthesis, characterization, stability, and C−H activation reactivity of complex 3 and its analogues.…”
mentioning
confidence: 99%